Pengaruh Variasi Produk, Orientasi Belanja dan Citra Merek terhadap Minat Beli pada Produk Makanan SugarWhisk - Octavian Hartono (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2025)
This research aims to analyze the influence of product variation, shopping orientation, and brand image on consumer purchase intention for SugarWhisk food products. The study employed a quantitative approach with an explanatory survey design, involving 200 respondents selected using purposive sampling based on their experience of purchasing or being familiar with SugarWhisk products. Data were collected through an online questionnaire using a 1–5 Likert scale and analyzed using a multiple linear regression model with SPSS version 26 software. The results showed that, partially, product variation, shopping orientation, and brand image had a significant positive effect on purchase intention, with brand image being the dominant factor. Simultaneously, the three independent variables jointly had a significant effect on purchase intention, with an adjusted R² of 0.587, indicating that 58.7% of the variation in purchase intention is explained by these three factors. These findings confirm the importance of diverse product development strategies, understanding consumer shopping orientation, and strengthening brand image to increase purchase intention and consumer loyalty. This research provides practical contributions for SugarWhisk owners in formulating effective marketing strategies, while also opening opportunities for further research on other factors such as price, promotion, and distribution channels.